Islet‐specific CD8+ T cells gain effector function in the gut lymphoid tissues via bystander activation not molecular mimicry. Issue 1 (1st November 2022) - Okada, Mirei; Zhang, Vivian; Loaiza Naranjo, Jeniffer D; Tillett, Bree J; Wong, F Susan; Steptoe, Raymond J; Bergot, Anne‐Sophie; Hamilton‐Williams, Emma E
Abstract: Type 1 diabetes (T1D) is caused by aberrant activation of autoreactive T cells specific for the islet beta cells. How islet‐specific T cells evade tolerance to become effector T cells is unknown, but it is believed that an altered gut microbiota plays a role. Possible mechanisms include bystander activation of autoreactive T cells in the gut or "molecular mimicry" from cross‐reactivity between gut microbiota‐derived peptides and islet‐derived epitopes. To investigate these mechanisms, we use two islet‐specific CD8 + T cell clones and the non‐obese diabetic mouse model of type 1 diabetes. Both insulin‐specific G9C8 cells and IGRP‐specific 8.3 cells underwent early activation and proliferation in the pancreatic draining lymph nodes but not in the Peyer's patches or mesenteric lymph nodes. Mutation of the endogenous epitope for G9C8 cells abolished their CD69 upregulation and proliferation, ruling out G9C8 cell activation by a gut microbiota derived peptide and molecular mimicry. However, previously activated islet‐specific effector memory cells but not naïve cells migrated into the Peyer's patches where they increased their cytotoxic function. Oral delivery of butyrate, a microbiota derived anti‐inflammatory metabolite, reduced IGRP‐specific cytotoxic function. Thus, while initial activation of islet‐specific CD8 + T cells occurred in the pancreatic lymph nodes, activated cells trafficked through the gut lymphoid tissues where they gained additional effector function via non‐specific bystander activation influenced by the gut microbiota. Type 1 diabetes is caused by aberrant activation of autoreactive T cells specific for the islet beta cells, but how these cells evade tolerance to become effector T cells is unknown. This study investigated whether islet‐specific T cells are activated in the gut via cross‐reactive bacterial derived peptides (molecular mimicry) or by non‐specific bystander activation. While initial activation of islet‐specific CD8 + T cells only occurred in the pancreatic lymph nodes, activated cells migrated to the Peyer's patches where they gained additional effector function under the influence of the gut microbiota: